Viability and functionality of Lacticaseibacillus rhamnosus and Bifidobacterium spp. in yoghurt - Buys, E.M. (Elna Maria) (University of Pretoria, 2025)
Thesis (PhD (Food Science))--University of Pretoria, 2025.